`d/(dx)cos^-1(x)=-1/sqrt(1-x^2)`

using above

`y=cos^-1(sin^-1(t))`

`y'=(-1)/sqrt(1-(sin^-1(t))^2) * d/(dt) sin^-1(t)`

`y'=(-1)/sqrt(1-(sin^-1(t))^2) * (1/sqrt(1-t^2))`

`y'=(-1)/(sqrt(1-t^2)sqrt(1-(sin^-1(t))^2))`

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now